2019
DOI: 10.1016/j.rpor.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose verification of an X-ray based blood irradiator using EBT3 radiochromic films calibrated using Gamma Knife machine

Abstract: Aim: Blood irradiators (BI) initial acceptance testing and routine annual dosimetry checks require radiation dose measurements in order to comply with regulatory requirements. Background: Traditionally thermoluminescence dosimeters (TLD) have been used to measure the dose. The EBT3 film is reported to be a better dosimeter for low energy X-rays than its predecessors EBT2 and EBT. To the best of our knowledge, the use of EBT3 films to perform dosimetry on X-ray based BI has not been reported yet. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…It measured the unknown dose based on the calibration of the standard curve. Soliman et al 14 , suggested that EBT3 provided more accurate results compared to TLD while Howard et al 15 indicated that EBT Gafchromic film provided more advantages to measure radiation dose. However, according to Najafi et al 16 , different findings were obtained on the dose measurement using Gafchromic film were due to the different factors such as the method for film digitation, the type of calibration curve used, or the uncertainty factor of gamma cell dose might cause deviation of the absorbed dose measurement.…”
Section: Discussionmentioning
confidence: 99%
“…It measured the unknown dose based on the calibration of the standard curve. Soliman et al 14 , suggested that EBT3 provided more accurate results compared to TLD while Howard et al 15 indicated that EBT Gafchromic film provided more advantages to measure radiation dose. However, according to Najafi et al 16 , different findings were obtained on the dose measurement using Gafchromic film were due to the different factors such as the method for film digitation, the type of calibration curve used, or the uncertainty factor of gamma cell dose might cause deviation of the absorbed dose measurement.…”
Section: Discussionmentioning
confidence: 99%
“…These models include the drive module of the stepper motor, the air pressure acquisition module, the liquid crystal communication and decoding module, the interpolation calculation module and so on. The user application calls these underlying driver functions in an orderly manner and performs corresponding operations according to the designed software workflow [24][25][26].…”
Section: Software Designmentioning
confidence: 99%
“…Therefore, film dosimetry is relatively simple, efficient, and less time-consuming. The commercially available Gafchromic film , (International Specialty Products, Inc., Wayne, NJ) has also been used for this purpose but it has several limitations like UV sensitivity, temperature sensitivity, and post irradiation instability. Also, its high cost restricts its use in routine dosimetry practice in the blood irradiator. In this context, we have attempted to develop novel diacetylene (DA)-based colorimetric film dosimeters for the measurement of radiation dose and dose distribution in blood irradiation.…”
Section: Introductionmentioning
confidence: 99%